Business Information Services (Tanzania) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Business Information Services (BIS) changes the lives of Tanzanian farmers and is a pioneering project that seeks to empower farmers and strengthen rural economies through e-business